Using insulin pumps in diabetes : a guide for nurses and other health professionals - Rodgers, Jill (John Wiley, 2008)
Insulin pump therapy is now a well-established option for treating diabetes. This method of insulin delivery offers the opportunity for people with diabetes to manage their diabetes confidently and competently to achieve good glycaemic control and a better quality of life. Using Insulin Pumps in Diabetes covers all aspects of insulin pump therapy in a clear and informative style, and is an essential guide for all health professionals involved in caring for people with diabetes using insulin pumps. Using Insulin Pumps in Diabetes explores issues such as the advantages and disadvantages of insul.